Mastering the art of French cooking - Beck, Simone; Louisette Bartholle; Child, Julia (New York Knopf, 1961)
Illustrates the ways in which classic French dishes may be created with American foodstuffs and appliances.
Vol. 2 by Julia Child and Simone Beck
Keywords: Cookery, French